2014
DOI: 10.1016/j.cell.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Dom34 Rescues Ribosomes in 3′ Untranslated Regions

Abstract: SUMMARY Ribosomes that stall before completing peptide synthesis must be recycled and returned to the cytoplasmic pool. The protein Dom34 and cofactors Hbs1 and Rli1 can dissociate stalled ribosomes in vitro, but the identity of targets in the cell is unknown. Here we extend ribosome profiling methodology to reveal a high-resolution molecular characterization of Dom34 function in vivo. Dom34 removes stalled ribosomes from truncated mRNAs, but, in contrast, does not generally dissociate ribosomes on coding sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
445
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(511 citation statements)
references
References 68 publications
55
445
1
Order By: Relevance
“…These results suggest that the stalled ribosome at the 5th codon position might adopt a more compact conformation than the others. Supporting this notion, recent studies demonstrated that the length of footprints could be influenced by ribosome dynamics [20,21].…”
Section: Ribosome Profiling Reveals Post-initiation Pausingmentioning
confidence: 65%
“…These results suggest that the stalled ribosome at the 5th codon position might adopt a more compact conformation than the others. Supporting this notion, recent studies demonstrated that the length of footprints could be influenced by ribosome dynamics [20,21].…”
Section: Ribosome Profiling Reveals Post-initiation Pausingmentioning
confidence: 65%
“…Recently, it was shown that after a termination event, 40S subunits, and probably also 80S ribosomes, could scan along the mRNA downstream or upstream to the next AUG position (64). Ribosome profiling methodology also revealed the possibility that 80S ribosomes scan downstream after translating a cistron in yeast (65). These observations suggest that the scanning mode of 70S or 80S ribosomes might be a universal ribosomal feature of the ribosomal translation process.…”
Section: Discussionmentioning
confidence: 86%
“…Experiments without CHX, on the other hand, report positive correlations of varying magnitude (Fig 1D, 0x Gerashchenko NAR points and purple labels). Experiments by Pop [36], Lareau [26], Nedialkova [29], Guydosh [35] and Gardin [33] produce weak to moderate correlations, but experiments by Gerashchenko [34], Jan [41], Williams [42], Weinberg [38], and Young [37] produce fairly strong and highly statistically significant correlations.…”
Section: Pretreatment With Cycloheximide Consistently Changes Enrichmmentioning
confidence: 99%
“…An alternative experimental protocol uses an optimized harvesting and flash-freezing process that allows CHX pretreatment to be omitted [15,17,26,29,[33][34][35][36][37][38]. Experiments performed with this protocol have revealed that treatment with CHX affects several high-level characteristics of footprinting data, including the distribution of lengths of nuclease-protected fragments in mammalian cells [39] and the amount of enrichment in ribosome density at the 5' end of coding sequences in yeast [34].…”
Section: Introductionmentioning
confidence: 99%